Challenges and Readiness of Islamic Education Teachers in Innovative Teaching and Learning - Suhid, Asmawati; Naser, Mohd Yusri Mohd; Ahmad, Abd. Muhsin; Abah, Noreha Che; Jusoh, Rosnani; Zaremohzzabieh, Zeinab (SCAD Independent, 2021)
The importance of Islamic education in building generations and society is undeniable. The field of Islamic education is not static but is constantly evolving as time goes by. In this paper, the author explored the technological innovations in today's world of education as well as the effects of Islamic Education teachers. The paper also discussed the barriers to implement technological education in Islamic education. Because of the current advent and emerging developments of technology and the impact of globalization, the paper offered possible solutions for Islamic educational systems and educational policymakers so as not to miss and fail the momentum of development. This study contributes towards strengthening the Islamic education system to engage in any innovation and transformation that may take place.